El manuscrit més antic de la Vita et passio sancti desiderii de Sisebut copiat pel sacerdot Isarn de Vic i altres còdexs realitzats pel mateix amanuense - Alturo i Perucho, Jesús (Miscel·lània litúrgica catalana, 2019)
Identification of the oldest surviving manuscript of the Vita et passio sancti Desiderii written by Sisebut, King of the Visigoths, which was copied in the late 10th century by the priest Isarn and kept in a passionary for the use of the Vic Cathedral. This fragment, now an incomplete bifolio, is conserved in the notable collection of codex fragments at the Vic Episcopal Library, frag. XXIV3. The text of this passionary is presented in this paper, pointing out its variant readings with respect to the most modern editions. Other codices copied by Isarn, a diploma scribe and codex amanuensis, are also identified, including some Homiliae XL in Euangelia by Saint Gregory the Great and some mass lectionaries. All these fragments have been recovered from bindings from Santa Maria de Moià, Sant Julià de Vilatorta, Santa Eugènia de Berga and Sant Boi de Lluçanès.